Kongres Ulama Perempuan Indonesia (KUPI) and Mubādalah Approach in Interpreting the Gender Biased-Qur'anic Verses - Junaidi, Akhmad Arif (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2023)
Conventional interpretation of the Quran often leads to the understanding that the verses are gender biased. This study is intended to discuss the mubādalah approach used by Kongres Ulama Perempuan Indonesia (KUPI) in interpreting the verses of the Qur’an that are considered gender bias. The question is how the Qur’an can be interpreted and how it can be explained. This study is a library study, focusing entirely on the existing library data. The study uses descriptive analysis with a hermeneutic approach, a tafsir analysis that considers the context of interpretation. This study concluded that the mubādalah approach that becomes the “official approach” of KUPI is relevant for interpreting gender biased-verses of the Qur’an. It is because the traditional and conventional interpretation makes it as if the verses of the Qur’an subordinate women, maltreating women in their relationship with men. Interpretation of the Quranic verses considered gender biased with the mubādalah approach in the context of the KUPI struggle is an appropriate advocative interpretation model for the improvement and fairness of gender relations.